Respostas

2013-12-12T19:24:04-02:00
x+3y=5 ( multiplica por  - 2)
-2x - 6y = - 10    (agora soma com a outra)
2x-y= - 4
------------------------
- 7 y = - 14 (-1)
7y = 14
y = 2      (encontramos y , basta substituir em qualquer outra equação para encontrar x)

x+3y=5
x + 3.2 = 5
x +6 = 5
x = -1

solução ( x = -1 e y = 2)
 

2013-12-12T19:24:42-02:00
X+3y=5
2x-y=-4

x=5-3y

2.(5-3y)-y = -4
10-6y-y=-4
10+4=7y
y=14/7
y=2

x=5-3y
x=5-3.2
x=-1

C.E.:
substituir valores:
2.-1-2=-4
-2-2=-4
-4=-4 (v)

X = -1 E Y= 2